The creation of goal scoring opportunities at the 2015 women`s world cup - Scanlan, M.; Harms, C.; Cochrane Wilkie, J.; Maayah, F. (International Journal of Sports Science & Coaching, 2020)
Women`s international football is growing in terms of popularity, but to date there is limited published research in women`s football and even less that describes effective attacking strategies and the creation of goal scoring opportunities (GSO). The purpose of this research was to investigate and assess the factors related to the creation of GSO that led to a Top 4 position Canada Women`s World Cup 2015. Video footage of each match (n = 52) from the Women`s World Cup (Canada 2015) was analysed using SportsCode Software. The results revealed that the middle third of the pitch was the most effective area for gaining possession and creating GSO. The average time taken to create a GSO was under twelve seconds. The findings of the study can be used by coaches to design training sessions and interventions to successfully create GSO in women`s football. The data from the research may influence the tactical set up of women`s international football teams and help to evolve the game in the same way that research into the men`s game has.